Calcium Activity of Upper Thoracic Dorsal Root Ganglion Neurons in Zucker Diabetic Fatty Rats - Ghorbani, Marie Louise (Hindawi Publishing Corporation, 2013)
The aim of the present study was to examine the calcium activity of C(8)-T(5) dorsal root ganglion (DRG) neurons from Zucker diabetic fatty rats. In total, 8 diabetic ZDF fatty animals and 8 age-matched control ZDF lean rats were employed in the study. C(8)-T(5) dorsal root ganglia were isolated bilaterally from 14 to 18 weeks old rats, and a primary culture was prepared. Calcium activity was measured ratiometrically using the fluorescent Ca(2+)-indicator Fura-2 acetoxymethyl ester. All neurons were stimulated twice with 20 mM K(+), followed by stimulation with either 0.3 or 0.5 μM Capsaicin, alone or in combination with algogenic chemicals (bradykinin, serotonin, prostaglandin E2 (all 10(−5) M), and adenosine (10(−3) M)) at pH 7.4 and 6.0. Neurons from diabetic animals exhibited an overall increased response to stimulation with 20 mM K(+) compared to neurons from control. Stimulation with Capsaicin alone caused an augmented response in neurons from diabetic animals compared to control animals. When stimulated with a combination of Capsaicin and algogenic chemicals, no differences between the two groups of neurons were measured, neither at pH 7.4 nor 6.0. In conclusion, diabetes-induced alterations in calcium activity of the DRG neurons were found, potentially indicating altered neuronal responses during myocardial ischemia.